Kinetic, volumetric and structural effects induced by liquid Ga penetration into ultrafine grained Al. (15th October 2015) - Naderi, Mehrnoosh; Peterlechner, Martin; Schafler, Erhard; Divinski, Sergiy V.; Wilde, Gerhard
Graphical abstract: Abstract: Kinetic, volumetric and structural effects induced by penetration of liquid Ga in ultrafine grained (UFG) Al produced by severe plastic deformation using high-pressure torsion were studied by isothermal dilatometric measurements, electron microscopy, atomic force microscopy and X-ray diffraction. Severe plastic deformation changed the distribution of impurities and their segregation was revealed by transmission electron microscopy. Two-stage length changes of UFG Al were observed which are explained by counteracting effects of expansion due to grain boundary segregation of Ga and contraction due to precipitation and recrystallization. After applying Ga, the kinetics of the liquid Ga penetration in UFG Al is studied in-situ in the electron microscope by the "first appearance" method and the time scales are in agreement with those inducing the volumetric changes.